Translanguaging Approach in English Classroom: Sentiment Analysis of Multilingual Indian Teachers' Perspective - Raya Ali; Michael Raj (CV. Eureka Murakabi Abadi, 2023)
Recent developments in India, the National Education Policy 2020, promote using the home language or mother tongue as the medium of instruction until Grade 5 and beyond. This paper explores the attitudes of multilingual teachers in India toward using translanguaging in English language teaching. Forty-five samples were collected, and the researcher measured thirteen translanguaging parameters to assess the attitudes of multilingual teachers. Using the VADER method, the researcher converted the translanguaging corpus and identified positive, negative, neutral, and compound sentiment scores. The results showed that most respondents had a neutral sentiment toward translanguaging. The researcher used a heat map to visualize the data, producing four clusters labeled Positive, Neutral, Negative, and Compound Sentiments of translanguaging. It can be concluded that adopting translanguaging might help create a more inclusive and powerful educational environment in multilingual countries like India because language ideologies influence how people perceive linguistic skills and practices.